(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article focuses on family culture, conscious entry into family life, willingness to perform family duties, high appreciation of the family’s place in life, development of family values in the spiritual heritage of the people, attitude towards relatives in the composition and formation of interpersonal relations in the family